Experimental and modeling study of compressive creep in 3D-woven Ni-based superalloys. (15th August 2018) - Cho, Hoon-Hwe; Erdeniz, Dinc; Sharp, Keith W.; Dunand, David C.
Abstract: Micro-architectured Ni-based superalloy structures, with Ni-20Cr-3Ti-2Al (wt.%) composition and γ/γ′-microstructure, are created by a multi-step process: (i) non-crimp orthogonal 3D-weaving of ductile, 202 μm diameter Ni-20%Cr wires, (ii) gas-phase alloying with Al and Ti, (iii) simultaneous transient-liquid phase (TLP) bonding between wires and homogenization within wires via interdiffusion, (iv) solutionizing to create a single-phase solid solution, and (v) aging to precipitate the γ′ phase. The creep behavior of these 3D-woven γ/γ′ nickel-based superalloys is studied under uniaxial compression via experiments at 825 °C and via finite element (FE) analysis, using a 3D model of the woven structures obtained through X-ray micro-tomography. The creep strain rate for the woven Ni-based superalloy is higher than that for the bulk superalloy due to the lower solid volume fraction of the woven structure, while the creep exponents are identical. The compressive creep behavior is sensitive to the geometry of the woven structures: fewer wires perpendicular to the load and fewer bonds between wires cause lower creep resistance of the woven structure, due to a reduction in load transfer from the longitudinal wires (which are primarily load-bearing) and the perpendicular wires. Creep buckling of longitudinal wires drastically reduces creep resistance of the woven structure, confirming the importance of maintaining longitudinal wires vertical and parallel to the uniaxial compression direction. Finally, reducing wire cross-section, e.g., via oxidation, reduces creep resistance. The oxidation kinetics of the wire structures at 750, 825, and 900 °C displayed parabolic rate constants comparable to commercial Ni-based superalloys, but indicates that up to 35% of the wire cross-section is oxidized after 7 days at 825 °C, such that oxidation-resistant coatings are needed for long-term use in oxidative environment. Graphical abstract: Image 1